High Cognitive Load During Cross-Examination: Does It Improve Detection of Children's Truths and Lies?. Issue 2 (4th March 2017) - Saykaly, Christine; Crossman, Angela; Talwar, Victoria
Abstract : The current study used a high cognitive load cross-examination procedure to determine whether this would improve undergraduate students' ability to detect deception in children aged 9 to 12 years. The participants ( n = 88) were asked to determine whether children's accounts of an event included a true denial, false denial, true assertion or false assertion about a game played during a home visit occurring one week prior. Overall, the high cognitive load cross-examination did not improve detection rates, in that participants were at chance level for both direct examination (49.4%) and cross-examination (52.3%). Accuracy for true stories was greater than for false stories. Cross-examination improved the detection rates of the false stories, but worsened the accuracy for the true stories. The participants did however rate younger children's true reports to be more credible and believable than their false reports. Participants rated older children's false reports as more credible and believable than their true reports.